Medical Management of Diverticular Disease - Knott, Liam; Reickert, Craig A. (Clinics in Colon and Rectal Surgery, 2018)
This article reviews the current literature supporting the non-surgical options for treatment in acute uncomplicated diverticulitis, complicated diverticulitis, and options for prevention of recurrent diverticulitis.
Keywords: diverticular disease; medical management